Struktur Upacara Adat Perkawinan Peranakan Tionghoa di Teluknaga Tangerang - Feby Yoana Siregar (JURNAL RUPA, 2017)
This study aims to determine the structure of traditional Chinese crossbreed in Indonesia wedding ceremonies. The research data is the result of informant interview. The method used in this research is descriptive qualitative method by using ceremonial theory and acculturation theory.The author chose this title because it is one of the unique traditions in Indonesia. This tradition is a blend of Chinese culture, Betawi and Sunda. Cio Tou is one of the traditional wedding tradition procession in Teluknaga Tangerang. The tradition of Cio Tou exists only in the tradition of the Chinese crossbreed customs in Teluknaga Tangerang. The results obtained in this research are 7 stages of traditional ceremony in Chinese crossbreed marriage that is the selection of soul mate, applying, dowry, youth evening, Cio Tou tradition, wedding reception, and custom after marriage.